Mixture analysis of paintings with Raman spectroscopic imaging and chemometrics - Phipps, Caitlyn E. (2014)
Conservation science is a eld that utilizes scienti c analysis for material identi cation tounderstand, conserve, and preserve culturally and/or historically important objects. Withinconservation science, we are focused on material identi cation using Raman spectroscopy.This work presented is divided into two projects, both utilizing Raman spectroscopy andchemometric algorithms for identi cation of pigments that are found in paintings. In the rst project, we developed a calibrated Raman spectral library and spectral comparisonprogram, which includes 15 pigments that can be found in modern artist materials suchas paints, markers, and ink pens. The second project involved the use of mathematicalalgorithms to digitally extract pure component spectra from Raman spectra of mixtures.Subsequently, by combining the tools developed in these two projects, we were able toidentify, without physical separation, the pigments utilized in the creation of paintings.